Construction And Validation of a Scale For Measuring Aggression In Adolescents - Malik, Mohd Aamier; Mustafa, Assuam; Govil, Punita (International Journal of Psychosocial Rehabilitation, 2019)
The scarcity of psychometric scales has been a barrier to progress in the field of research on aggressive behavior in adolescents. The present study elucidates the process of constructing and validating an aggression scale that measures the attitude of adolescents towards aggression. The researcher employed a standardized approach to construct the aggression scale for the purpose of assessing levels of aggression among secondary school students. The present study involved the application of both exploratory and confirmatory factor analyses to the responses of the sample of adolescents, ranging in age from 11 to 14 years, with a total sample size of N=1200 participants. In order to assess the reliability of the scale, Alpha Cronbach and Composite reliability has been established. The items were divided into four factors having satisfactory factor loading values. All of the items that make up the factors were thoroughly analyzed and labeled as “Attitude towards aggression, Psychosocial and cognitive assessment, Behavioral assessment, and Social relationship”. The four factors comprising the final Aggression Scale (AS) all demonstrated satisfactory Alpha Cronbach and Composite reliability. To verify the four-component structure of the aggression scale that was obtained through exploratory factor analysis, confirmatory factor analysis was subjected to the data obtained from the second sample of secondary school students (N=1200) with the help of IBM-AMOS Version 23.0. The model fit indices of the scale were adequate (RMSEA=0.042), indicating a good model fit (CFI=0.97, TLI= 0.97). The validity of the tool was measured through three types: i) Content validity ii) Convergent validity and iii) Divergent validity. All the parameters of assessing validity were satisfactory for the development of the aggression scale. The aggression scale offers a valid and reliable instrument for assessing adolescents’ aggressive behavior.